Analysis of pediatric adverse reactions to transfusions. Issue 1 (25th September 2017) - Vossoughi, Sarah; Perez, Gabriela; Whitaker, Barbee I.; Fung, Mark K.; Stotler, Brie
Abstract : BACKGROUND: Children are known to be physiologically and biochemically different from adults. However, there are no multi‐institutional studies examining the differences in the frequency, type, and severity of transfusion reactions in pediatric versus adult patients. This study aims to characterize differences between pediatric and adult patients regarding adverse responses to transfusions. STUDY DESIGN AND METHODS: This is a retrospective data analysis of nine children's hospitals and 35 adult hospitals from January 2009 through December 2015. Included were pediatric and adult patients who had a reported reaction to transfusion of any blood component. Rates are reported as per 100, 000 transfusions for comparison between pediatric and adult patients. RESULTS: Pediatric patients had an overall higher reaction rate compared to adults: 538 versus 252 per 100, 000 transfusions, notably higher for red blood cell (577 vs. 278 per 100, 000; p < 0.001) and platelet (833 vs. 358 per 100, 000; p < 0.001) transfusions. Statistically higher rates of allergic reactions, febrile nonhemolytic reactions, and acute hemolytic reactions were observed in pediatric patients. Adults had a higher rate of delayed serologic transfusion reactions, delayed hemolytic transfusion reactions, and transfusion‐associated circulatory overload. CONCLUSION: Pediatric patients had double the rate of transfusion reactions compared to adults. The nationally reported data on reaction rates are consistent with this study's findings in adults but much lower than the observed rates for pediatric patients. Future studies are needed to address the differences in reaction rates, particularly in allergic and febrile reactions, and to further address blood transfusion practices in the pediatric patient population.